The Importance Of Teaching Social Ideal Ideas In Eastern Philosophy (Texas Journal of Philology, Culture and History, 2024)
The article provides information about the importance of the relationship between the identified ideal and reality. This article highlights important historical, philosophical, and religious ideals. The essence of these ideals, their significance between society and man is analyzed. Philosophical issues related to the dialectic between ideal and reality and their application in life are discussed